(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
One of the effective teaching technologies in the modern education system is problem-based learning. Problem-based learning corresponds to the goals of creative and active education of the individual. The essence of problem-based learning is the independent acquisition of new knowledge by creating a problem situation.